The Candida albicans Pho4 Transcription Factor Mediates Susceptibility to Stress and Influences Fitness in a Mouse Commensalism Model - Urrialde, Verónica; Prieto, Daniel; Pla, Jesús; Alonso-Monge, Rebeca (Frontiers in Microbiology, 2016)
The Pho4 transcription factor is required for growth under low environmental phosphate concentrations in Saccharomyces cerevisiae. A characterization of Candida albicans pho4 mutants revealed that these cells are more susceptible to both osmotic and oxidative stress and that this effect is diminished in the presence of 5% CO2 or anaerobiosis, reflecting the relevance of oxygen metabolism in the Pho4-mediated response. A pho4 mutant was as virulent as wild type strain when assayed in the Galleria mellonella infection model and was even more resistant to murine macrophages in ex vivo killing assays. The lack of Pho4 neither impairs the ability to colonize the murine gut or alter the localization into the gastrointestinal tract. However, we found that Pho4 influenced the colonization of C. albicans in the mouse gut in competition assays; pho4 mutants were unable to attain high colonization levels when it was inoculated together with the wild type strain. Moreover, pho4 mutants displayed a reduced adherence to the intestinal mucosa in a competitive ex vivo assays with wild type cells. In vitro competitive assays also revealed defects in fitness for this mutant compared to the wild type strain. Thus, Pho4 a transcription factor involved in phosphate metabolism is required for adaptation to stress and fitness in C. albicans.